Respuesta :

Answer:

Step-by-step explanation:

The standard form of an equation for a straight line is y=mx+b, where m is the slope and b is the y-intercept (the value of y when x = 0).

We can calculate the slope from the two given points, (6,-3) and (-6,-5).  Slope is Rise/Run, where Rise is the change in y and Run is the change in x.

From the two given points, starting at (-6,-5) and going to (6,-3):

Rise = (-3 - (-5)) = +2

Run = (6 - (-6)) = 12

Rise/Run (slope) = 2/12 or 1/6

The equation becomes y = (1/6)x + b

We can find b by enterieng either of the two given points and solving for b.  I'll pick (6,-3):

y = (1/6)x + b

-3 = (1/6)*(6) + b

-3 = 1 + b             [Now you can see why I chose (6,-3)]

b = -4

The equation is y = (1/6)x - 4

Check this with a DESMOS graph (attached).

Ver imagen rspill6